Magnetic field effects on neutrino production in microquasars - Reynoso, Matias Miguel (2008)
We investigate the effects of magnetic fields on neutrino production in microquasars.We calculated the steady particle distributions for the pions and muons generated in p-gamma and p-p interactions in the jet taking the effects of all energy losses into account. The obtained neutrino emission is significantly modified due to the synchrotron losses suffered by secondary pions and muons. The estimates made for neutrino fluxes arriving on the Earth imply that detection of high-energy neutrinos from the vicinity of the compact object can be difficult. However, in the case of windy microquasars, the interaction of energetic protons in the jet with matter of dense clumps of the wind could produce detectable neutrinos. This is because the pions and muons at larger distances from the compact object will not be affected by synchrotron losses.